52 Patterns of late gadolinium enhancement in chronic kidney disease: a predictor of clinical outcome data?. (June 2018) - Price, Anna M; Hayer, Manvir K; Fyyaz, Saad A; Moody, William E; Ferro, Charles J; Townend, Jonathan N; Steeds, Richard P; Edwards, Nicola C
Abstract : Introduction: Patterns of late gadolinium enhancement (LGE) using cardiac MRI (CMR) are integral to characterising myocardial disease and are prognostic of adverse cardiovascular outcome in ischaemic and non-ischaemic disease. In chronic kidney disease (CKD), CMR has re-defined Ërenal cardiomyopathy demonstrating high rates of myocardial abnormalities specifically hypertrophy and myocardial fibrosis which are present from the earliest stages of CKD. The aim of this study was to: i) assess the frequency and patterns of LGE in CKD and ii) whether LGE predicts clinical outcome in CKD. Methods: Patients with CKD (stage 2–4; eGFR 89–15 ml/min/1.73 m 2 ) undergoing CMR (1.5T) as part of prospective research between 2005–2017 were included. Subjects were recruited from renal clinics, had controlled hypertension and no history of cardiovascular disease or diabetes. Gadolinium was administered if eGFR >15 ml/min/1.73m 2 between 2005–2012 and eGFR >30 ml/min/1.73m 2 between 2012–2017 due to changes in policy and MHRA guidance.Patterns of LGE were assessed by two blinded observers. Results: In total, 178 patients (mean age 54 years, male 59%) underwent CMR (table 1). Gadolinium was administered in 134 subjects with LGE present in 46 (35%) subjects; right ventricular insertion point (RVIP) LGE n=22, mid wall/diffuse n=16, subendocardial n=4, and epicardial (n=4) (figure 1). There were no differences in LV structure and function between those with and without LGE (table 2). The presence of LGE was not predicted by age, odds ratio (OR) 1.268 (95% confidence interval;CI 0.900–1.786), male gender OR 1.567 (CI 0.586–4.191), eGFR OR 1.300 (CI 0.963–1.756), EF OR 0.953 (CI 0.879–1.034) or cQT OR 1.080 (CI 0.933–1.250). There were 15 deaths over the median follow-up of 11.1 years with no difference in patients with LGE (13% vs 10%). The presence of LGE did not confer a poorer outcome for survival (p=0.14) (figure 2). There were no cases of nephrogenic systemic fibrosis. Conclusions: Patterns of LGE are present in a third of patients with early stage CKD without symptomatic cardiovascular disease but did not predict all-cause mortality. These data may reflect a stable low risk cohort and high rates of RVIP-LGE which is associated with lower risk profile than myocardial LGE in other diseases.